An Evaluation of Intranasal Sufentanil and Dexmedetomidine for Pediatric Dental Sedation - James M. Hitt; Toby Corcoran; Kelly Michienzi; Paul Creighton; Christopher Heard (MDPI AG, 2014)
Conscious or moderate sedation is routinely used to facilitate the dental care of the pre- or un-cooperative child. Dexmedetomidine (DEX) has little respiratory depressant effect, possibly making it a safer option when used as an adjunct to either opioids or benzodiazepines. Unlike intranasal (IN) midazolam, IN application of DEX and sufentanil (SUF) does not appear to cause much discomfort. Further, although DEX lacks respiratory depressive effects, it is an α2-agonist that can cause hypotension and bradycardia when given in high doses or during prolonged periods of administration. The aim of this feasibility study was to prospectively assess IN DEX/SUF as a potential sedation regimen for pediatric dental procedures. After IRB approval and informed consent, children (aged 3-7 years; n = 20) from our dental clinic were recruited. All patients received 2 μg/kg (max 40 μg) of IN DEX 45 min before the procedure, followed 30 min later by 1 μg/kg (max 20 μg) of IN SUF. An independent observer rated the effects of sedation using the Ohio State University Behavior Rating Scale (OSUBRS) and University of Michigan Sedation Scale (UMSS). The dentist and the parent also assessed the efficacy of sedation. Dental procedures were well tolerated and none were aborted. The mean OSUBRS procedure score was 2.1, the UMSS procedure score was 1.6, and all scores returned to baseline after the procedure. The average dentist rated quality of sedation was 7.6 across the 20 subjects. After discharge, parents reported one child with prolonged drowsiness and one child who vomited at home. The use of IN DEX supplemented with IN SUF provided both an effective and tolerable form of moderate sedation. Although onset and recovery are slower than with oral (PO) midazolam and transmucosal fentanyl, the quality of the sedation may be better with less risk of respiratory depression. Results from this preliminary study showed no major complications from IN delivery of these agents.